Social Media Optimization and Artificial Intelligence in Increasing the Capacity of Digital Promotion of MSMEs In Petukangan, Pesanggrahan, South Jakarta - Lies Hendrawan Krisnawati; Rosalia Andayani; Albiansyah Albiansyah; Irma Maria Dulame; Sri Rahayu (FKIP, Universitas Palangka Raya, 2026)
This Community Service (PKM) activity is motivated by the low capacity of MSME actors and start-up business people in utilizing social media and Artificial Intelligence (AI) technology as a means of digital promotion. These limitations include low digital literacy, limited capabilities for visual content production, weak marketing communication strategies, and inconsistent business social media management. This study aims to improve participants' understanding and skills in optimizing social media and utilizing AI to support business promotion. The approach used is a qualitative descriptive approach, with observation, interviews, documentation, direct practice, discussion, mentoring, and training evaluation. The activity was held in Petukangan, Pesanggrahan District, South Jakarta, with participants consisting of MSME actors, students, and the general public. The results showed that 85% of participants experienced an increase in understanding of digital marketing strategies.In comparison, 78% were able to create promotional content independently with the help of AI, especially through Bing Image Creator and ChatGPT. These findings show that integrating social media and AI can increase creativity, improve content production efficiency, and enhance the visual appeal of MSME promotion. The novelty of this activity lies in integrating AI-based visual design training with strengthening the digital entrepreneurship mindset. Thus, this training model can be an applicable, adaptive, and relevant MSME empowerment strategy for digital economy transformation.